Comparison of two murine models of thrombosis induced by atherosclerotic plaque injury - Hechler, Béatrice; Gachet, Christian (Thrombosis and Haemostasis, 2011)
Arterial thrombosis occurs at sites of erosion or rupture of atherosclerotic vascular lesions. To better study the pathophysiology of this complex phenomenon, there is a need for animal models of localised thrombosis at sites of atherosclerotic lesions with closer resemblance to the human pathology as compared to commonly used thrombosis models in healthy vessels. In the present study, we describe and compare a new model of thrombosis induced by atherosclerotic plaque rupture in the carotid artery from ApoE-/- mice using a suture needle to a milder model of ultrasound-induced plaque injury. Needle injury induces atherosclerotic plaque rupture with exposure of plaque material and formation of a thrombus that is larger, nearly occlusive and more stable as compared to that formed by application of ultrasounds. These two models have common features such as the concomitant involvement of platelet activation, thrombin generation and fibrin formation, which translates into sensitivity toward both antiplatelet drugs and anticoagulants. On the other hand, they display differences with respect to the role of the platelet collagen receptor GPVI, the plaque rupture model being less sensitive to its inhibition as compared to the ultrasound-induced injury, which may be related to the amount of thrombin generated. These models represent an improvement as compared to models in healthy vessels and may help identify specific plaque triggers of thrombosis. They should therefore be useful to evaluate new antithrombotic targets.
Keywords: Animal models; antiplatelet agents; atherosclerosis; arterial thrombosis; atherothrombosis